2022
DOI: 10.1371/journal.pone.0265822
|View full text |Cite
|
Sign up to set email alerts
|

Keep your budget together! Investigating determinants on risky decision-making about losses

Abstract: The present study investigates the influence of framing, different amounts to lose, and probabilities of a risky and sure choice option, time limits, and need on risky decision-making. For a given block of trials, participants were equipped with a personal budget (number of points). On each trial within a block, a specific initial amount is possibly taken from the budget by the outcome of a gamble or the choice of a sure loss option. The goal was to avoid losing points from the budget for not falling below a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Once again, the psychophysical data collection approach has been shown to be an excellent method for measuring framing effects (see also, e.g., Guo et al, 2017 ; Diederich et al, 2020 ; Roberts et al, 2021 ; Wyszynski and Diederich, 2022 ). In addition to framing, we found other effects influencing the proportion of choosing the gamble.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…Once again, the psychophysical data collection approach has been shown to be an excellent method for measuring framing effects (see also, e.g., Guo et al, 2017 ; Diederich et al, 2020 ; Roberts et al, 2021 ; Wyszynski and Diederich, 2022 ). In addition to framing, we found other effects influencing the proportion of choosing the gamble.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…It is also possible that other effects not considered in the current studies, as well as further interaction effects (e.g., 3-way-interactions), influence choice behavior. For instance, we know from previous studies that short time limits for making the risky choice enhance the framing effect (e.g., Guo et al, 2017 ; Diederich et al, 2018 , 2020 ; Wyszynski and Diederich, 2022 ). In the current study, the effect of time limits was not moderated by scores of the psychometric instruments (see experiment 1), but it is well possible that individual cognitive-styles and risk-styles influence the relationship between time and framing or other interactions.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research has shown that a need defined similarly as in the current study can serve as a reference point in various decision-making scenarios. Thus, need has been shown to influence decisions as well as charitable donations and to moderate framing effects (e.g., Bauer, 2019;Bauer et al, 2022;Diederich et al, 2020;Weiß et al, 2017;Wyszynski et al, 2020;Wyszynski & Diederich, 2022).…”
Section: Summary and Discussionmentioning
confidence: 99%